Detection method for quantitative analysis of carbon fiber skin-core structure degree

Through the method of epoxy resin embedding and ion beam cutting combined with scanning electron microscopy, the degree of skin core structure of carbon fiber was quantitatively analyzed, solving the problem of analysis in the prior art, and achieving high-precision, environmental protection and efficient detection effects.

CN119804529APending Publication Date: 2025-04-11INST OF COAL CHEM CHINESE ACAD OF SCI

Patent Information

Application Number
CN202510030227.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively analyze the degree of the leather core structure of carbon fiber, which leads to difficulties in guiding and adjusting the oxidation process and affects the mechanical properties of carbon fiber products.

Method used

The carbon fiber was embedded with epoxy resin, and the embedded samples were cut and polished with an ion beam cutting instrument. The morphology was observed with a scanning electron microscope. By calculating the contrast between the skin and core structure of the fibers in the SEM diagram, the degree of the skin core structure was quantitatively analyzed.

Benefits of technology

High-precision quantitative analysis of the structural degree of carbon fiber leather core is achieved, the sample preparation process is simplified, the cost is reduced, the use of hazardous chemicals is avoided, and the detection efficiency and success rate are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119804529A_ABST
    Figure CN119804529A_ABST
Patent Text Reader

Abstract

The invention discloses a detection method for quantitatively analyzing the skin-core structural degree or structural uniformity of carbon fibers, and belongs to the technical field of carbon fiber detection. The invention aims to solve the problems of complexity, high cost, high requirement and poor precision of the current detection method for the carbon fiber sheath core. The method comprises the following steps: embedding a to-be-detected fiber bundle by taking epoxy resin as a matrix, and sequentially carrying out ion beam cutting and ion beam polishing on an embedded sample by virtue of a focusing mode and a non-focusing mode of an ion beam cutting instrument to obtain a polished sample of which the fiber cross section or longitudinal section is parallel to the surface of the sample. And then observing the fiber morphology under a scanning electron microscope, and carrying out quantitative analysis on the skin-core structure degree according to the axial or radial contrast difference of the fiber in an SEM graph. The detection method combining resin embedding, ion beam'cutting and polishing 'sample preparation and scanning electron microscope observation and analysis is adopted, the process is simple, convenient and rapid, no chemical reagent pollution exists, the sample preparation success rate is high, the detection efficiency is high, and the whole process cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon fiber detection, and in particular relates to a detection method for quantitatively analyzing the degree or structural uniformity of carbon fiber skin-core structure. Background Art

[0002] Carbon fiber has a series of excellent properties such as high specific strength, high specific modulus, high temperature resistance, corrosion resistance, fatigue resistance, electrical conductivity, thermal conductivity, good biocompatibility, etc. It is widely used in aerospace, national defense, nuclear energy, wind power, transportation, body products, medical equipment and other industries. The pre-oxidation (also known as stabilization) process is a key stage in the preparation of carbon fiber, and it is also the most energy-consuming and longest-residence section in the preparation of carbon fiber. In this stage, the carbon fiber precursor undergoes a series of complex chemical reactions such as cyclization, dehydrogenation, and oxidative cross-linking, gradually converting the linear macromolecular chain into a heat-resistant ladder and cross-linked structure, which is convenient for further high-temperature carbonization treatment. In order to reduce the production cost of carbon fiber, a high-temperature and rapid oxidation process is often used in the pre-oxidation stage. However, cyclization is a thermal reaction-controlled process, and oxidation is an oxygen diffusion-controlled process; high temperature and rapid oxidation processes are prone to form a dense ladder structure on the fiber surface, further hindering the diffusion rate of oxygen to the fiber core, and easily forming a structural inhomogeneity within the cross-section of the pre-oxidized fiber. The carbonization process further exacerbates the differences in the cross-sectional structure of the oxidized fiber, which ultimately affects the mechanical properties of the carbon fiber product. Therefore, analyzing, especially quantitatively analyzing, the skin-core structure of carbon fiber can help to provide targeted guidance and adjustment for the oxidation process, so as to prepare high-performance carbon fiber products with homogeneous cross-sectional structure and excellent mechanical properties.

[0003] The precursor filament of polyacrylonitrile carbon fiber is composed of microfibrils, fibril structures arranged and stacked along the fiber axis to form a quasi-crystalline structure. The pre-oxidation and carbonization process will preserve the order of the precursor structure. The precursor and pre-oxidized fibers are frozen and brittle by liquid nitrogen, and the cross-sections formed by cutting the carbon fiber with a blade or freezing and brittle by liquid nitrogen are composed of nanoparticles and pore structures. It is difficult to observe the inhomogeneity of the structure under an electron microscope, and it is difficult to make targeted quantitative guidance for the pre-oxidation process. In addition, the diameter of high-performance carbon fibers is often low (≤5.5μm), and the diffusion channels of oxygen and cracking products during the pre-oxidation process are short, which makes the difference in the radial pre-oxidation degree of the fibers low. The radial structural differences of carbon fibers obtained by conventional sample preparation methods are difficult to observe by electron microscopy (such as Figure 2 shown).

[0004] At present, there are three main methods for quantitatively detecting the degree of pre-oxidation or carbon fiber skin-core structure. First, sulfuric acid, formic acid, dimethyl sulfoxide or dimethylformamide are used to pre-treat the pre-oxidized fiber, and the parts with insufficient oxidation degree and linear structure such as limited core trapezoidal or cross-linked structure at both ends of the fiber can be etched or dissolved, and the skin-core structure degree is analyzed under a scanning electron microscope. Chinese patent CN201611114005.2 discloses a method for detecting the skin-core structure of polyacrylonitrile pre-oxidized fiber, in which 2-4 cm long short-cut fibers are boiled and refluxed in a 20-60% sulfuric acid solution for 0.1-2.0h to obtain hollow fibers with etched cores, rinsed with deionized water and dried, and then observed under a scanning electron microscope to further calculate the skin-core structure degree. This method consumes a certain amount of sulfuric acid solution each time, and the low-concentration sulfuric acid solution produced by flushing is a hazardous chemical that will cause certain pollution to the environment. In addition, the etching temperature and time of sulfuric acid solution for structures with different precursors and different oxidation degrees are different, and the basic conditions need to be explored through multiple etching tests. Otherwise, only the structural uniformity of the same batch of products can be compared and analyzed. In addition, the fibers after drying are messy and not bundled, and it is difficult to ensure that the fiber cross section is perpendicular to the sample stage, which has a certain adverse effect on the observation of the fiber cross section under an electron microscope.

[0005] Secondly, the epoxy resin embedded carbon fiber samples are cut / sliced ​​and polished, and the structural order or element content of the fiber cross section is detected and analyzed along the diameter direction using spectral and ray equipment. Chinese patent CN201010284020.8 discloses a method for determining the radial heterogeneous structure of carbon fiber. The cross section of the resin embedded carbon fiber after slicing is subjected to multi-point Raman spectroscopy analysis. The 1360cm -1 With 1580cm -1 The relative intensity ratio of the two scattering peaks I 1360cm -1 / I 1580cm -1 , and the corresponding degree of graphitization is obtained, and then the change of the degree of graphitization along the fiber diameter is analyzed. Relative to the carbon fiber diameter of 5 to 7 μm, the Raman spectrum spot diameter is limited (≥1 μm), and it is impossible to accurately grasp the degree of the skin-core structure, or grasp the critical position where the structure becomes heterogeneous. Chinese patent CN202010392578.1 discloses a method for characterizing the skin-core structure of pre-oxidized silk, which implements grinding, polishing and other corrections and gold spraying treatment on the end face of the resin-embedded fiber sample, and uses an electron probe to scan the fiber cross section to obtain the distribution of oxygen content along the radial direction of the fiber. When using spectral and ray analysis instruments to characterize the degree of pre-oxidation of the fiber, it is necessary not only to repeat multiple times and sample multiple groups for averaging to reduce the structural deviation caused by individual differences; but also such tests are time-consuming and expensive.

[0006] Third, the resin-embedded fiber sample is ground and polished, and the fiber cross-sectional morphology or structure is analyzed using a microscope. Chinese patent CN202010200070.7 discloses a method for measuring the skin-core structure of polyacrylonitrile pre-oxidized filaments and carbon fiber by metallographic microscope. After the resin-embedded fiber sample is mechanically ground with sandpaper and polished with abrasive paste, the fiber cross section is observed using a metallographic microscope. For pre-oxidized filaments with a low degree of pre-oxidation, the skin-core difference under the metallographic microscope is significant, and this method can be used to determine its skin-core structure; for pre-oxidized filaments with a relatively appropriate or high degree of pre-oxidation, the skin-core structure difference under the metallographic microscope is very weak, and it is difficult to use this method for quantitative analysis. For resin-embedded carbon fiber samples, mechanical cutting, sandpaper grinding, and grinding paste polishing are used. Due to the "brittle" nature of carbon fiber, in most cases, the fiber cross section under a scanning electron microscope after grinding and polishing is fragmented, and it is difficult to obtain a sample with a flat carbon fiber cross section; and the skin-core structure of a carbon fiber sample with a flat cross section is also difficult to observe under a metallographic optical or scanning electron microscope. Chinese patent 201410075559.0 discloses a method for microscopic characterization and detection of carbon fiber uniformity. The resin-embedded carbon fiber sample is mechanically cut and thinned to 5 to 200 nm by argon ion polishing, and the fiber cross-section and longitudinal section are observed and analyzed by transmission electron microscopy. The structural differences of the carbon fiber cross section and the characteristics of the skin-core ring can be described or observed more accurately, and the change of the OA angle along the radial direction of the fiber can be obtained, thereby obtaining the uniformity of the texture in the fiber cross section. The disadvantages are that the thickness requirements of the sample are relatively strict, the sample preparation method is relatively complicated, the sample preparation success rate is low (less than 30%) and the sample preparation duration is long (18 to 36 hours). Summary of the invention

[0007] In view of the problems that the current detection methods of carbon fiber skin-core are complicated, costly, demanding and poor in precision, the present invention provides a detection method for quantitatively analyzing the skin-core structure degree of carbon fiber, wherein the carbon fiber is embedded in an epoxy resin as a matrix, and the resin-embedded fiber sample is cut and polished by an ion cutting instrument, and a SEM morphology image is obtained by scanning electron microscope morphology observation, and the skin-core structure degree of the fiber is calculated according to the carbon fiber diameter and the core diameter.

[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0009] A method for quantitatively analyzing the degree of carbon fiber skin-core structure comprises the following steps:

[0010] Step 1, take a carbon fiber bundle of 30 to 50 mm, fix it to both ends of the hollow paper frame with glue, and place it in the mold to keep the fiber bundle vertical;

[0011] Step 2, embedding the carbon fiber with epoxy resin, and slowly pouring a mixture of epoxy resin and curing agent mixed evenly in a certain proportion into a mold after standing for degassing for 5 minutes, and curing for 0.5 to 10 hours at a temperature of 25 to 120° C. and a relative pressure of -0.09 to 0.01 MPa to obtain an embedded sample;

[0012] Step 3, cutting and polishing the embedded sample using an ion beam cutter;

[0013] Step 4, using a scanning electron microscope to observe and photograph the morphology of the embedded fiber polished by the ion beam;

[0014] Step 5, calculating the corresponding skin-core structure degree according to the different contrasts of the carbon fiber skin and core structures in the SEM image.

[0015] Further, the step 5 calculates the corresponding skin-core structure degree according to the different contrasts of the carbon fiber skin and core structures in the SEM image, specifically: according to the SEM images of the transverse and longitudinal sections of the fiber, the calculation method is as follows:

[0016]

[0017] Among them, F is the skin-core structure of the fiber, R 芯部 is the core radius, R 纤维 is the radius of the fiber.

[0018] Furthermore, in step 3, the embedded sample is cut and polished by using an ion beam cutter, specifically, the cutting and polishing are performed along the cross section or longitudinal section of the carbon fiber.

[0019] Furthermore, when an ion beam cutter is used to cut and polish the embedded sample in step 3, the cutting stage uses a focusing mode of the ion beam cutter, and the polishing stage uses a non-focusing mode of the ion beam cutter.

[0020] Furthermore, the ion beam cutting instrument in step 3 uses a focused argon ion beam in the cutting stage of the sample preparation process, and uses an unfocused argon ion beam in the polishing stage. The focused argon ion beam has higher energy, smaller ion beam diameter, and limited range of action, and is suitable for cutting samples; the unfocused ion beam has lower energy, a larger processing surface or range, and a uniform processing force, so that the surface of the sample after processing is smoother and flatter, and is suitable for polishing the surface of the sample after cutting.

[0021] Furthermore, when the embedded sample is cut and polished by an ion beam cutter in step 3, the angle between the ion beam and the surface of the embedded sample is 6-15° in the cutting stage and 1-6° in the polishing stage. Preferably, the cutting angle is 7-12° and the polishing angle is 2-5°.

[0022] Furthermore, in step 3, when an ion beam cutter is used to cut and polish the embedded sample, the ion beam voltage is 1 to 12 kV; wherein the ion beam cutting voltage is 6 to 12 kV and the time is 1 to 3 h, and the ion beam polishing voltage is 1 to 6 kV and the time is 1 to 5 h. Preferably, the cutting voltage is 5 to 10 kV and the polishing voltage is 2 to 5 kV. If the voltage is too high, the ion beam will have too much impact on the sample surface, which may easily cause local overheating and thus structural changes; if the voltage is too low, the ion beam energy is low, and the cutting and polishing effects are limited.

[0023] Furthermore, the sample obtained in step 3 has a thickness of 1 to 10 mm and a cross-sectional area of ​​1 to 200 mm. 2 ; When the sample thickness is less than 1mm, the ion beam is likely to have an adverse effect on the crystallization behavior of the sample. When the thickness is greater than 10mm, it is not conducive to scanning analysis. The preferred cross-sectional shape can be circular or rectangular, with a cross-sectional side length or diameter less than 15mm.

[0024] Furthermore, in step 4, the observation voltage of the scanning electron microscope is 10 to 20 kV, and the magnification is 5000 to 15000 times.

[0025] Furthermore, the mass ratio of the epoxy resin to the curing agent is 100:7-24, the epoxy value of the epoxy resin is 0.4-0.9, and an amine curing agent is used for curing.

[0026] Furthermore, the carbon fiber is polyacrylonitrile-based, asphalt-based or viscose-based carbon fiber.

[0027] Furthermore, the mold in step 1 is a plastic or rubber mold, preferably a rubber mold.

[0028] Furthermore, the paper frame in step 1 is to ensure that the axial directions of the fibers in the fiber bundle are all along a fixed direction.

[0029] Furthermore, in step 2, the epoxy resin can be cured under curing conditions with gradually increasing curing temperature and vacuum degree to shorten the curing time and reduce bubbles in the sample.

[0030] Furthermore, the ion beam in step 3 is an argon ion beam, whose moderate relative molecular weight and inertness are the preferred characteristics for ion beam cutting and polishing. If the relative molecular weight of the ion beam is too high, the microstructure of the sample surface will change; especially when the sample thickness is thin, the ion beam with a higher atomic number will make the lattice structure of the sample tend to be amorphous.

[0031] Furthermore, the ion beam cutting instrument is an argon ion single beam, dual beam, triple beam or multi-beam cutting instrument. Preferably, the number of ion beams contained is dual beam or triple beam; too few ion beams will not only affect the cutting efficiency, but also the cutting effect, and will form an inclined and uneven section on the sample end face; too many ion beams will cause mutual interference between the ion beams, thereby reducing the cutting effect.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] (1) The whole process of sample preparation and testing of the method of the present invention uses only epoxy resin for fiber embedding, and does not use hazardous chemicals such as sulfuric acid, formic acid, dimethyl sulfoxide or dimethylformamide, which will not cause harm to the environment and is more environmentally friendly than etching or dissolving the core method.

[0034] (2) The method of the present invention uses an ion beam cutting instrument, which integrates sample cutting and polishing, and does not cause material consumption caused by mechanical grinding and polishing; the sample preparation process is simple and fast, with a 100% sample preparation success rate, which is simpler, more efficient, and consumes less materials than the traditional sample preparation process.

[0035] (3) The method of the present invention uses an ion beam cutting instrument, which has high precision in sample surface preparation and can distinguish subtle structural differences between the skin and the core, that is, even slight differences between the skin and the core can be detected; however, structures with slight differences between the skin and the core are difficult to analyze by etching or metallographic microscopy.

[0036] (4) The method of the present invention adopts a method combining an ion beam cutting instrument and a scanning electron microscope, which can not only avoid the deviation caused by individual differences, but also its detection cost is much lower than that of detection methods such as Raman spectroscopy and electron probe analyzer. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0038] Figure 1 Schematic diagram of the process of the present invention.

[0039] Figure 2 SEM image of the cross section of polyacrylonitrile-based carbon fiber obtained by conventional method;

[0040] Figure 3 AFM image of the cross section of polyacrylonitrile-based carbon fiber obtained by ion beam cutting;

[0041] Figure 4SEM morphology of polyacrylonitrile-based carbon fiber obtained by the method of the present invention. DETAILED DESCRIPTION

[0042] In order to gain a deeper understanding of the present invention, we will provide a comprehensive and detailed description of the present invention. However, the present invention has multiple implementations and is not limited to the specific examples listed herein. The presentation of these examples is intended to deepen the comprehensive understanding of the disclosure of the present invention.

[0043] After the resin-embedded fiber sample obtained by the present invention is cut and polished by an argon ion beam, the degree of its skin-core structure can be obtained by analyzing the SEM images of the fiber's transverse and longitudinal sections. The calculation method is shown in formula (1):

[0044]

[0045] Among them, F is the skin-core structure of the fiber, R 芯部 is the core radius, R 直径 is the radius of the fiber.

[0046] Embodiment 1:

[0047] Step 1, take a 30 mm long polyacrylonitrile-based carbon fiber bundle obtained by pre-oxidation at 280°C for 20 minutes and carbonization at 1500°C for 10 minutes, fix it at both ends of a hollow paper frame with 502 glue, and then place it in a rubber-plastic mold to keep the fiber bundle vertical;

[0048] Step 2, weighing 5 g of homemade epoxy resin a (epoxy value 0.87) and ethylenediamine curing agent in a mass ratio of 100:10, stirring evenly, standing for degassing for 5 minutes, and then slowly pouring into the mold; curing at room temperature and normal pressure for 6 hours to obtain an embedded sample;

[0049] Step 3, cutting the embedded sample using the focusing mode of the dual ion beam cutter, maintaining an angle of 12° between the ion beam and the surface of the embedded sample, cutting at 9 kV for 1.5 h to obtain an ion beam cut sample; adjusting the ion beam cutter to a non-focusing mode to perform ion beam polishing on the surface of the ion beam cut sample, maintaining an angle of 5° between the ion beam and the surface of the ion beam cut sample, polishing at 5 kV for 1 h to obtain an ion beam polished embedded fiber sample φ8 mm×H1.81 mm;

[0050] Step 4, using a scanning electron microscope to observe and photograph the embedded fiber sample polished by ion beam, the SEM voltage is selected to be 20 kV, and the magnification is 5000 times, so that a certain number of fiber cross sections are presented in the field of view and photographed, so as to facilitate the calculation of the corresponding skin-core structure degree;

[0051] Step 5, by Figure 3 (a) AFM images and Figure 4(a) As shown in the SEM morphology, the sample cross section has more ion erosion textures, and the skin-core structure of the fiber cross section is easy to observe; according to formula (1), 5 carbon fiber cross sections were selected for calculation and averaged, and the skin-core structure degree of the carbon fiber under the heat treatment condition was 53.92%.

[0052] Embodiment 2:

[0053] Step 1, take a 35 mm long polyacrylonitrile-based carbon fiber bundle obtained by oxidation at 270°C for 30 minutes and carbonization at 1500°C for 10 minutes, fix it to both ends of a hollow paper frame with 502 glue, and then place it in a rubber-plastic mold to keep the fibers vertical;

[0054] Step 2, weighing about 5 g of epoxy resin 618 (epoxy value 0.48-0.54) and curing agent 593 in a mass ratio of 100:30, stirring evenly, standing for degassing for 5 minutes, and then slowly pouring into the mold; curing at 25°C and -0.04MPa for 1 hour, and then improving the curing conditions to 60°C, -0.08MPa, and 30 minutes to obtain an embedded sample;

[0055] Step 3, cutting the embedded sample using the focusing mode of the three-ion beam cutter, maintaining an angle of 9.5° between the ion beam and the surface of the embedded sample, cutting at 8 kV for 2 h to obtain an ion beam cut sample; adjusting the ion beam cutter to a non-focusing mode to perform ion beam polishing on the surface of the ion beam cut sample, maintaining an angle of 4° between the ion beam and the surface of the ion beam cut sample, polishing at 3 kV for 1.5 h to obtain an ion beam polished embedded fiber sample φ8 mm×H1.75 mm;

[0056] Step 4, using a scanning electron microscope to observe and photograph the embedded fiber sample polished by ion beam, the SEM voltage is selected to be 20 kV, and the magnification is 5000 times, so that a certain number of fiber cross sections are presented in the field of view and photographed, so as to facilitate the calculation of the corresponding skin-core structure degree;

[0057] Step 5, by Figure 3 (b) AFM images and Figure 4 (b) As shown in the SEM morphology, the sample cross section has less ion erosion texture and the skin-core structure of the fiber cross section is easy to observe. According to formula (1), 5 carbon fiber cross sections were selected for calculation and averaged, and the skin-core structure degree of the carbon fiber under the heat treatment condition was 28.20%.

[0058] Embodiment 3:

[0059] Step 1, take a 30 mm long polyacrylonitrile-based carbon fiber bundle obtained by oxidation at 260°C for 45 minutes and carbonization at 1500°C for 10 minutes, fix it to both ends of a hollow paper frame with 502 glue, and then place it in a rubber-plastic mold to keep the fibers vertical;

[0060] Step 2, weighing 5 g of epoxy resin 6101 (epoxy value 0.41-0.47) and curing agent triethylenetetramine in a mass ratio of 100:7, stirring evenly, standing for degassing for 5 minutes, and then slowly pouring into the mold; curing at 25°C and -0.02MPa for 2 hours, raising the curing temperature to 85°C for 15 minutes to obtain the embedded sample;

[0061] Step 3, cutting the embedded sample using the focusing mode of the three-ion beam cutter, maintaining an angle of 8° between the ion beam and the surface of the embedded sample, cutting at 7 kV for 2.5 h to obtain an ion beam cut sample; adjusting the ion beam cutter to a non-focusing mode to perform ion beam polishing on the surface of the ion beam cut sample, maintaining an angle of 3.5° between the ion beam and the surface of the ion beam cut sample, polishing at 2.5 kV for 1.8 h to obtain an ion beam polished embedded fiber sample φ8 mm×H1.78 mm;

[0062] Step 4, using a scanning electron microscope to observe and photograph the embedded fiber sample polished by ion beam, the SEM voltage is selected to be 15 kV, and the magnification is 5000 times, so that a certain number of fiber cross sections are presented in the field of view and photographed, so as to facilitate the calculation of the corresponding skin-core structure degree;

[0063] Step 5, by Figure 3 (c) AFM images and Figure 4 (c) As shown in the SEM morphology, the ion erosion texture of the sample cross section is very weak, and the skin-core structure of the fiber cross section is easy to observe. According to formula (1), 5 carbon fiber cross sections were selected for calculation and averaged, and the skin-core structure degree of the carbon fiber under the heat treatment condition was 19.02%.

[0064] Embodiment 4:

[0065] Step 1, take a 35 mm long polyacrylonitrile-based carbon fiber bundle obtained by oxidation at 260°C for 60 minutes and carbonization at 1500°C for 10 minutes, fix it at both ends of a hollow paper frame with 502 glue, and then place it in a rubber-plastic mold to keep the fibers vertical;

[0066] Step 2, weighing about 5 g of epoxy resin 6101 (epoxy value 0.41-0.47) and 593 curing agent in a mass ratio of 100:24, stirring evenly, standing and degassing for 5 minutes, and then slowly pouring into the mold; curing at 25°C and -0.02MPa for 1 hour, and then improving the curing conditions to 80°C, -0.08MPa, and 20 minutes to obtain the embedded sample;

[0067] Step 3, cutting the embedded sample using the focusing mode of the three-ion beam cutter, maintaining an angle of 7° between the ion beam and the surface of the embedded sample, cutting at 6 kV for 2.8 h to obtain an ion beam cut sample; adjusting the ion beam cutter to a non-focusing mode to perform ion beam polishing on the surface of the ion beam cut sample, maintaining an angle of 2.5° between the ion beam and the surface of the ion beam cut sample, polishing at 2 kV for 2 h to obtain an ion beam polished embedded fiber sample φ8 mm×H1.93 mm;

[0068] Step 4, using a scanning electron microscope to observe and photograph the embedded fiber sample polished by ion beam, the SEM voltage is selected to be 15 kV, and the magnification is 5000 times, so that a certain number of fiber cross sections are presented in the field of view and photographed, so as to facilitate the calculation of the corresponding skin-core structure degree;

[0069] Step 5, by Figure 3 (d) AFM images and Figure 4 (d) As shown in the SEM morphology, the ion erosion texture of the sample cross section is very weak, and the skin-core structure of the fiber cross section is easy to observe. According to formula (1), 5 carbon fiber cross sections were selected for calculation and averaged, and the skin-core structure degree of the carbon fiber under the heat treatment condition was 11.58%.

[0070] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the illustrative specific embodiments of the present invention are described above to facilitate the understanding of the present invention by the technical personnel in the field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For the ordinary technical personnel in the field, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

Claims

1. A method for quantitatively analyzing the degree of the skin-core structure of carbon fiber, characterized in that: The following steps are involved: Step 1, keeping the fiber bundle vertically fixed; Step 2, embedding the carbon fiber with a mixture of epoxy resin and curing agent to obtain an embedded sample; Step 3, cutting and polishing the embedded sample using an ion beam cutter; Step 4, using a scanning electron microscope to observe and photograph the morphology of the embedded fiber polished by the ion beam; Step 5, calculating the corresponding skin-core structure degree according to the different contrasts of the carbon fiber skin and core structures in the SEM image.

2. A method for quantitatively analyzing the skin-core structure of carbon fiber according to claim 1, characterized in that: The step 5 calculates the corresponding skin-core structure degree according to the different contrasts of the carbon fiber skin and core structures in the SEM image. Specifically, it is obtained by analyzing the SEM images of the transverse and longitudinal sections of the fiber. The calculation method is as follows: Among them, F is the skin-core structure of the fiber, R 芯部 is the core radius, R 纤维 is the radius of the fiber.

3. A method for quantitatively analyzing the degree of the skin-core structure of carbon fiber according to claim 1, characterized in that: In step 3, the embedded sample is cut and polished by using an ion beam cutter, specifically, cutting and polishing are performed along the cross section or longitudinal section of the carbon fiber.

4. A method for quantitatively analyzing the degree of the skin-core structure of carbon fiber according to claim 1, characterized in that: When an ion beam cutter is used to cut and polish the embedded sample in step 3, the cutting stage adopts the focusing mode of the ion beam cutter, and the polishing stage adopts the non-focusing mode of the ion beam cutter.

5. The method for quantitatively analyzing the skin-core structure of carbon fiber according to claim 1, characterized in that: When the embedded sample is cut and polished by an ion beam cutter in step 3, the angle between the ion beam and the surface of the embedded sample is 6 to 15° in the cutting stage and 1 to 6° in the polishing stage.

6. A method for quantitatively analyzing the skin-core structure of carbon fiber according to claim 1, characterized in that: When an ion beam cutter is used to cut and polish the embedded sample in step 3, the voltage of the ion beam cutter is 1 to 12 kV, wherein the ion beam cutting voltage is 6 to 12 kV and the time is 1 to 3 h, and the ion beam polishing voltage is 1 to 6 kV and the time is 1 to 5 h.

7. The method for quantitatively analyzing the skin-core structure of carbon fiber according to claim 1, characterized in that: In step 4, the observation voltage of the scanning electron microscope is 10-20 kV, and the magnification is 5000-15000 times.

8. The method for quantitatively analyzing the skin-core structure of carbon fiber according to claim 1, characterized in that: In step 2, a mixture of epoxy resin and curing agent is used to embed the carbon fiber to obtain an embedded sample. Specifically, the uniformly mixed mixture of epoxy resin and curing agent is allowed to stand for degassing for 5 minutes and then slowly poured into a mold, and cured for 0.5 to 10 hours at a temperature of 25 to 120° C. and a relative pressure of -0.09 to 0.01 MPa to obtain an embedded sample.

9. The method for quantitatively analyzing the skin-core structure of carbon fiber according to claim 1, characterized in that: The mass ratio of the epoxy resin to the curing agent is 100:7-24, and the epoxy value of the epoxy resin is 0.4-0.

9.

10. The method for quantitatively analyzing the skin-core structure of carbon fiber according to claim 1, characterized in that: The ion beam cutting instrument is an argon ion single ion beam, double ion beam, triple ion beam or multi-ion beam cutting instrument.

Citation Information

Patent Citations

  • Method for determining radial heterostructure degree of carbon fiber

    CN101949828A

  • A microscopic characterization detection method for the uniformity of carbon fiber

    CN103884551B

  • Polyacrylonitrile preoxidized fiber skin-core structure detection method

    CN106596614A

  • Method for measuring polyacrylonitrile pre-oxidized fiber and carbon fiber sheath-core structure by metallographic microscope

    CN111307804A

  • Characterization method of pre-oxidized fiber sheath-core structure

    CN111562279A

Cited By

  • On-line monitoring device and method for component ratio of composite filament

    CN120490301A